Unusual presentations of central nervous system myeloid sarcoma. Issue 6 (19th June 2022) - Chatterton, Sophie; Helou, Jacob; Drummond, James; Gill, Anthony J.; Ward, Christopher; Coyle, Luke; Kerridge, Ian; Ng, Karl
Abstract: Myeloid sarcoma (MS), also termed 'chloroma' or 'granulocytic sarcoma', is a tumour mass consisting of myeloid blasts occurring at an anatomical site other than the bone marrow. MS occurs in up to 8% of patients with acute myeloid leukaemia. While MS typically involves the skin or lymph nodes, almost any tissue can be affected, and symptoms largely depend on the organ involved and subsequent mass effect. We present a case series of patients that presented to a tertiary hospital with MS affecting the central nervous system over a 4‐month period. These three cases demonstrate the vast spectrum of clinical presentations of MS and, furthermore, show rare examples of intramedullary spinal cord involvement and disseminated intraparenchymal brain disease.